Willingness To Pay Rumah Tangga Dalam Membayar Biaya Pendidikan Menengah Unggulan di Kota Malang - M. Irfan Rosyadi; Sasongko Sasongko; Arif Hoetoro (Universitas Negeri Malang, 2016)
Importance of education to economic development and an understanding of households determine the educational services, these makes excellent secondary educational institutions in Malang greatly demanded, but the willingness to pay the cost of education questionable. This study used primary data from a questionnaire completed by 150 respondents, and then analyzed by multiple regression method to measure the value of willingness to pay as well as the dependent variables that influence. The study showed that an average household less willing to pay the cost of excellent secondary education. Income, number of dependents, education and access had a significant effect.Keywords: Willingness to pay, household, excellent secondary educationJEL Classification: D10, I24